KERAGAMAN GENETIK ALANG-ALANG (Imperata cylindrica (L.) Beauv.) BERDASARKAN MARKA INTER-SIMPLE SEQUENCE REPEATS (ISSR) - Dyah Subositi; Harto Widodo (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Alang-alang (Imperata cylindrica (L.) Beauv.) has been widely used as a medicinal plant to treat some diseases, such as fever, headache, and diuretic. Nowadays, there is no information of genetic diversity of this plant used in herbal formula by ethnic groups in Indonesia. The main objective of this study was to asses genetic diversity of alang-alang from 18 selected ethnic groups in Indonesia based on Inter Simple Sequence Repeats (ISSR). Location of sample collection was identified by using data on Research on Medicinal Plant (Ristoja) 2012. Total DNA genome was isolated and ISSR primer screening were done on collected samples. Ten selected ISSR primers produced 74 amplified DNA fragments 58, fragments (78.4 %) were polymorphic. Dice index similarity was used to construct UPGMA dendrogram. The genetic similarity indexing which among accessions was ranged from 70.5–90.5% thereby indicating a low level of genetic diversity occurred in alang-alang. The results of this study also showed that ISSR markers were able to genetically differentiate alang-alang accessions by which this information can be useful for further researchs such as for standardization of medicinal plants.